EVALUATION OF VAT COLLECTION ON TRADING THROUGH ELECTRONIC SYSTEM - Kusumabangsa, Gilang (Jurnal Akuntansi dan Keuangan Indonesia, 2021)
This research aims to evaluate the Value-added Tax (VAT) collection on trading through the electronic system (TTES) from the TTES VAT Collector’s perception, based on "The Four Maxims" tax collection principle. This research uses a qualitative research method with a case study approach. Data was collected using interview techniques with eight respondents from TTES VAT Collectors. The results showed that TTES VAT collection in Indonesia has fulfilled the equality, convenience and efficiency principles based on "The Four Maxims". However, the collection of TTES VAT in Indonesia has failed to meet the criterion of certainty, owing to uncertainties in the definition, the legal status of the collector, the method for calculating the tax basis, tax procedures, and the enforcement of fines.